2008
DOI: 10.1182/blood-2007-07-103697
|View full text |Cite
|
Sign up to set email alerts
|

PDGF, TGF-β, and FGF signaling is important for differentiation and growth of mesenchymal stem cells (MSCs): transcriptional profiling can identify markers and signaling pathways important in differentiation of MSCs into adipogenic, chondrogenic, and osteogenic lineages

Abstract: We compared the transcriptomes of marrow-derived mesenchymal stem cells (MSCs) with differentiated adipocytes, osteocytes, and chondrocytes derived from these MSCs. Using global gene-expression profiling arrays to detect RNA transcripts, we have identified markers that are specific for MSCs and their differentiated progeny. Further, we have also identified pathways that MSCs use to differentiate into adipogenic, chondrogenic, and osteogenic lineages. We identified activin-mediated transforming growth factor (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
401
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 535 publications
(434 citation statements)
references
References 53 publications
24
401
0
9
Order By: Relevance
“…To this end, we employed aSMA promoter as an indicator of myogenic phenotype 30 and selected several genes that are known to regulate contractile function, through the Rho or TGF-b1 pathways. In agreement with previous studies, 31,32 TGF-b1 induced MSC differentiation toward the myogenic lineage as shown by enhanced aSMA promoter activity and verified at the protein level by western blot and immunostaining. Blocking TGF-b1 receptor activity or knocking down the TGF-b1 mediators Smad2, Smad3 or Smad4 significantly decreased aSMA activity.…”
Section: Discussionsupporting
confidence: 92%
“…To this end, we employed aSMA promoter as an indicator of myogenic phenotype 30 and selected several genes that are known to regulate contractile function, through the Rho or TGF-b1 pathways. In agreement with previous studies, 31,32 TGF-b1 induced MSC differentiation toward the myogenic lineage as shown by enhanced aSMA promoter activity and verified at the protein level by western blot and immunostaining. Blocking TGF-b1 receptor activity or knocking down the TGF-b1 mediators Smad2, Smad3 or Smad4 significantly decreased aSMA activity.…”
Section: Discussionsupporting
confidence: 92%
“…Jian et al (2006) reported that TGFb1 induced BM-MSCs proliferation through a novel mechanism of cross-talk between the TGF-b and Wnt signaling pathways. Additionally, the combination of TGF-b, PDGF and bFGF was shown to support BM-MSCs growth in a serum-free medium up to 5 passages (Ng et al 2008). Based on these data, we believe that bFGF and TGFb1 may also be present in ESCM similar to those observed from a previous study because our conditioned medium was obtained from cell culture supernates of the same human ES cell line.…”
Section: Discussionsupporting
confidence: 72%
“…TGF-β family signaling may thus differentially regulate MSC proliferation through crosstalk with Wnt signaling, as demonstrated also in epithelial stem cells. Recently, using transcriptome analyses, Ng et al [96] predicted that signaling pathways mediated by TGF-β, platelet-derived growth factor (PDGF), and FGF play important roles in the proliferation of MSCs. Inhibition of any of these signals decreased the growth of MSCs, whereas a combination of these three factors enabled multiple passages of MSCs, suggesting that these signaling pathways are necessary and sufficient for MSC growth.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%